Molecular Radio-Oncology - Baumann, Michael; Krause, Mechthild; Cordes, Nils (Recent Results in Cancer Research, 2016)
This book concisely reviews our current understanding of hypoxia, molecular targeting, DNA repair, cancer stem cells, and tumor pathophysiology, while also discussing novel strategies for putting these findings into practice in daily clinical routine. Radiotherapy is an important part of modern multimodal cancer treatment, and the past several years have witnessed not only substantial improvements in radiation techniques and the use of new beam qualities, but also major strides in our understanding of molecular tumor biology and tumor radiation response. Against this backdrop, the book highlights recent efforts to identify reasonable and clinically applicable biomarkers using broad-spectrum tissue microarrays and high-throughput systems biology approaches like genomics and epigenomics. In particular, it describes in detail how such molecular information is now being exploited for diagnostic imaging and imaging throughout treatment using the example of positron emission tomography. By discussing all these issues in the context of modern radiation oncology, the book provides a broad, up-to-date overview of the molecular aspects of radiation oncology that will hopefully foster its further optimization.